EXPRESSING THE STYLISTIC DEVICE PERIPHRASIS IN LITERATURE - Abdullayeva, Zarina (Журнал иностранных языков и лингвистики, 2023)
This article deals with expressing the stylistic device periphrasis as a in literatures. The article analyzes the use of periphrasis as a stylistic device with examples.